Gross and histopathological characteristics of Anabas testudineus acquired from peat swamp and feeder canal of peat swamp forest in north Selangor, Malaysia - Nurnajwa Atiqah Md Sallehuddin,
The adaptability of fish species inhabiting extreme water condition has intrigued many studies in this area. However, there is no report on the morphological and histopathological changes of Anabas testudineus surviving in the North Selangor Peat Swamp Forest (NSPF). Hence, this study involved 13 adult Anabas testudineus fish procured from peat swamp site and feeder canal with the aim to compare the gross and histopathological changes of gills, liver and kidneys of these fishes in acidic (pH 3.24) and natural environment (pH 6.42) part of the forest reserve. Results showed no significant differences (p>0.05) in mean body weight, total body length and mean length of gills, liver and kidney between the two groups. Gill morphometric analysis in fishes from the peat swamp revealed shorter secondary lamellar length (SLL), less basal epithelial thickness (BET), shorter interlamellar distance (ID) which reduces total size of dead space, thicker secondary lamellar width (SLW). The proportion of the secondary lamellar available for gas exchange (PAGE) is higher in fishes from the peat swamp (42.6%) than those from the feeder canal (34.3%). Grossly, fishes captured from the peat swamp also displayed dull, opaque, darker colouration, more slimy and slippery epidermal. Additionally, these fishes displayed less well-defined ganoid shaped of the scale, hyperaemic and translucent ventral abdomen and the liver were peculiar bright orange in colour with rounded inferior margin and glistening capsule. Histopathological assessment revealed significant differences (p<0.05) in parameters such as detachment of epithelium and hyperplasia of goblet cells in gills, hepatocyte swelling or hydropic degeneration and intracytoplasmic lipid vacuoles in liver, pyknotic tubular epithelium and hydropic degeneration of renal tubules in kidneys between the two groups. In conclusion, Anabas fishes from two different sites showed changes in the liver grossly and histopathologically in gills, liver and kidneys. Therefore, the peat swamp environment has an impact on the gross and histopathology of selected organs of Anabas testudineus.